Efecto de la proporción de glucosa y gelatina en la aceptabilidad sensorial de gomitas masticables de pulpa de Vaccinium corymbosum - Guzmán Flores, Eduardo Yasert (2023)
The objective of this research is to determine the sensory acceptability of a jelly bean made of blueberry pulp from Chao district, Viru province, it was used: glucose, jelly, blueberry pulp, sorbitol and water in the initial formulation of the product. The target group of the product was the youth population. 5 formulations or treatments, varying their rates by weight: T1 (Jelly 2%, Glucose 38%) T2 (Jelly 4%, Glucose 36%, T3 (Jelly 6%, Glucose 34%) and T4 (Jelly 8%, Glucose 32%), keeping other ingredients such as sour blueberry poulp (40%), water (18%) and sorbitol (2%). The acceptance was compared regarding color, flavor, texture and general appearance. The result of the sensory evaluation indicated that the treatment accepted the most was T4 (Jelly 8%, glucose 32%), this teatment get a highest score in the amounts of the acceptance averages in all the attributes. The test of acceptance or rejection indicates that the product elaborated with the formulation more accepted has 55% of acceptance on the part of the consumer population, indicating the viability of production and marketing.